Genetic associations between weight at maturity and maturation rate with ages and weights at first and second calving in Canchim beef cattle - Gaviolli, V. R. N.; Buzanskas, M. E. [UNESP]; Cruz, V. A. R. [UNESP]; Savegnago, R. P. [UNESP]; Munari, D. P. [UNESP]; Freitas, A. R.; Alencar, M. M. (Springer Heidelberg, 2012)
Genetic parameters for weight at maturity (WM), maturation rate (MR), age and weight at first calving (AFC and WFC) and second calving (ASC and WSC) were estimated for females of the Canchim breed. The number of records per trait ranged from 1440 to 1923. The restricted maximum likelihood method was used and the statistical model included the fixed effect of contemporary group and the additive genetic and residual as random effects. The mean heritability estimate and respective standard errors were 0.34 +/- 0.05 (WM), 0.13 +/- 0.04 (MR), 0.14 +/- 0.04 (AFC), 0.44 +/- 0.06 (WFC), 0.16 +/- 0.06 (ASC) and 0.39 +/- 0.06 (WSC). The heritability estimate for WM and MR suggested that it would be possible to achieve changes in the animals' growth curve through selection, but the genetic correlation between these two traits suggested that there would be antagonism between them. Selection for WM would result in animals with later growth and would also affect individuals' sexual precocity. This was also seen from the genetic correlations between WM and the other traits, which ranged from 0.37 to 0.98; and between MR and the other traits, which ranged from -0.83 to -0.25. Selection to modify WM would be expected to result in correlated responses in AFC, WFC and WSC and a moderate response in ASC. Although the heritability estimate for MR was low, selection aimed for its increase might cause a large decrease in AFC, ASC and WFC and a moderate change in WSC, and this could be an alternative for improving the progeny's overall performance.
Keywords: Age at calving; asymptotic weight; Genetic correlation; Heritability; Weight at calving